PENERAPAN BUSINESS MODEL CANVAS DALAM STRATEGI PENGEMBANGAN USAHA WISATA KEBUN BINATANG TASTA ZOO TABANAN - Ni Wayan Listia Dewi; Ni Putu Noviyanti Kusuma; Jauzaa Maylia Suhendro (UNHI Press, 2026)
Strategic Development of Tasta Zoo Tabanan through the Application of the Business Model Canvas (BMC). This activity was initiated by the problem of suboptimal business development and digital marketing strategies at Tasta Zoo Tabanan, which potentially hindered its competitiveness in Bali's tourism. The method applied was a descriptive qualitative approach with triangulation techniques (observation, interviews, questionnaires), focused on implementing and validating the Business Model Canvas (BMC) framework to map and redesign the destination's business model. The activity resulted in a holistic BMC Version 2, with a core value proposition centered on conservation-based edutainment (education and entertainment) experiences. The partial implementation of BMC-based strategies, particularly in digital marketing and interactive education programs, proved to increase audience engagement on social media (e.g., a 408% increase in TikTok followers), visitor satisfaction, and operational revenue. The activity concludes that the BMC is an effective strategic tool for creating sustainable competitive advantage for educational tourism destinations, with main recommendations focusing on strengthening human resources, deepening partnerships, and technology integration.